Pengaruh Rasio Derajat Disentralisasi, Rasio Kemandirian Keuagan Daerah dan Rasio Tingkat Pembiayaan SiLPA terhadap Alokasi Belanja Modal di Kabupaten/Kota Sumatera Barat - Mulyani, Sri; Fitra, Halkadri (Jurnal Nuansa Karya Akuntansi, 2023)
This study aims to determine the extent to which the influence of the degree of decentralization ratio, the ratio of regional financial independence and the SiLPA financing ratio can affect the capital expenditure allocation of district/city governments in West Sumatra. Data analysis used multiple linear regression analysis. Based on partial testing, 1) it is found that the ratio of the degree of decentralization has a significant positive effect on the allocation of capital expenditure in districts/cities in West Sumatra Province. 2) The ratio of regional financial independence has a positive effect on the allocation of capital expenditures in districts/cities of West Sumatra Province. .3) finance in the form of the ratio of SiLPA financing rates has a positive and significant influence on the allocation of capital expenditures in districts/cities in West Sumatra Province.